An ultra-sensitive suboptimal protospacer adjacent motif enhanced rolling circle amplification assay based on CRISPR/Cas12a for detection of miR-183 - Lu, Zhiquan; Wang, Shijing; Li, Ping; Yang, Huasheng; Han, Sanyang; Zhang, Shaochong; Ma, Lan (Frontiers in Bioengineering and Biotechnology, 2024)
MicroRNAs (miRNAs) have been recognized as promising diagnostic biomarkers for Diabetic Retinopathy (DR) due to their notable up-regulation in individuals with the condition. However, the development of highly sensitive miRNAs assays for the rapid diagnosis of DR in clinical settings remains a challenging task. In this study, we introduce an enhanced CRISPR/Cas12a assay, leveraging suboptimal PAM (sPAM)-mediated Cas12a trans-cleavage in conjunction with rolling circle amplification (RCA). We found that sPAM performed better than canonical PAM (cPAM) in the detection of Cas12a-mediated ssDNA detection at low concentrations, and by replacing cPAM with sPAM in the padlock template of RCA, ultra-high sensitivity can be achieved, with a detection limit of 0.40 aM within 25 minutes and a linear range spanning from 1 aM to 1 pM. Notably, our assay exhibits exceptional specificity in detecting miR-183 from other miRNAs. Furthermore, we validate the applicability of our assay for the sensitive detection of miR-183 in clinical serum samples. This study introduces a groundbreaking assay with excellent performance through a simple modification, which not only addresses existing diagnostic challenges, but also opens exciting new avenues for clinical diagnosis in the realm of Diabetic Retinopathy.